1982
DOI: 10.2307/1540983
|View full text |Cite
|
Sign up to set email alerts
|

THE BIOLOGY OF A BROODING SEASTAR,LEPTASTERIAS TENERA, IN BLOCK ISLAND SOUND

Abstract: Leptasterias tenera (Stimpson) was sampled from a muddy habitat, 28-37 m deep, dominated by tubicolous amphipods. The seastars were seldom aggregated and had mean densities of 3-8 individuals per m 2 . L. tenera is holophagous, feeding primarily on small crustaceans which they capture with the pedicellariae and tube feet. Approximately half of the branched testes in mature males are degenerated or absent, but females usually have 10 lobate ovaries. Females initially brood embryos in their pyloric stomach and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

1984
1984
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 27 publications
(42 reference statements)
1
9
1
Order By: Relevance
“…However, O'Brien (1976) has suggested that brooding female Leptasterias littoralis may feed on fine particulate material and brooding Leptasterias hexactis, L. pusilla and L. tenera have occasionally been found with ingested prey (Osterud, 1918;Menge, 1974;Smith, 1981 ;Hendler and Franz, 1982). In the present study, however, Anasterias rupicola was shown to be an active predator at least in the later stages of brooding, feeding as frequently as do non-brooding A. rupicola.…”
Section: Discussioncontrasting
confidence: 50%
“…However, O'Brien (1976) has suggested that brooding female Leptasterias littoralis may feed on fine particulate material and brooding Leptasterias hexactis, L. pusilla and L. tenera have occasionally been found with ingested prey (Osterud, 1918;Menge, 1974;Smith, 1981 ;Hendler and Franz, 1982). In the present study, however, Anasterias rupicola was shown to be an active predator at least in the later stages of brooding, feeding as frequently as do non-brooding A. rupicola.…”
Section: Discussioncontrasting
confidence: 50%
“…Brooding may reduce parental fitness by limiting mobility and increasing vulnerability to predators (Strathmann 1985, Bosch & Slattery 1999. This limited mobility may also prevent or reduce feeding, leading to the use of somatic reserves (Chia 1969, Nimitz 1971, Menge 1974, 1975, Harrold & Pearse 1980, Hendler & Franz 1982, Jangoux 1982, Doughty & Shine 1997. Whereas reproductive investment is limited to the period of gametogenesis in species with pelagic larvae (Thorson 1950, Mileikovsky 1971, brooding parents also pay energetic costs for maintenance during brooding.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…A well-known example is the genus Leptasterias in northern temperate to Arctic regions (Fisher 1930, Chia 1969, Menge 1974, 1975, O'Brien 1976, Hendler & Franz 1982, Himmelman et al 1982, Boivin et al 1986, Chia & Walker 1991, Hamel & Mercier 1995. Leptasterias species brood during cold periods (Chia 1966, Himmelman et al 1982, and most are small (e.g.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Brooding in A. antarctica from Beagle Channel occurs during the coldest months of the year (austral winter), as it was reported for other populations (Gil et al, 2011;Laptikhovsky et al, 2015) and also for other asteroid such as Leptasterias polaris (Himmelman et al, 1982) and Leptasterias tenera (Hendler & Franz, 1982). During brooding and non-brooding period, there were females in two reproductive conditions simultaneously.…”
Section: Discussionmentioning
confidence: 56%